Application of oral evaluation techniques focused on the oral performance of students in intermediate intensive english II of the foreign languages Department of the University of El Salvador - Portillo Anaya, Sandra Carolina (Universidad de El Salvador, 2003)
The students’ attitude toward the different oral evaluation techniques plays an important role when they are involved in the development of the tasks discussed in the classroom. Since oral performance has been considered one of the most difficult and important skill for students in the process of learning English, and also for teachers in the process of teaching the foreign language, it is necessary to observe how effective the students’ speaking is in the target language, so that they are able to move on to new topics or to have the opportunity for feedback, improvement and also identify their own strengths and weak areas in oral performance. That is why in the present work it is made a general description of the most common oral evaluation techniques known by teachers who teach in the Language Department of the University of El Salvador the subject Intensive Intermediate English II. The purpose of this material is to inform teachers of English the positive and negative aspects of the oral evaluation techniques described in order to improve students oral performance. A special emphasis has been given to those oral evaluation techniques that are the most suitable with the Language Department education and population reality. Besides that, the important opinion of the teachers of the Language Department has been included, as well as their own valuable experience when using some of the oral evaluation techniques that are described in here.